2014
DOI: 10.1016/j.tcs.2013.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-orientation equilateral triangle matching of point sets

Abstract: Given a point set P and a class C of geometric objects, G C (P) is a geometric graph with vertex set P such that any two vertices p and q are adjacent if and only if there is some C ∈ C containing both p and q but no other points from P. We study G ▽ (P) graphs where ▽ is the class of downward equilateral triangles (ie. equilateral triangles with one of their sides parallel to the x-axis and the corner opposite to this side below that side). For point sets in general position, these graphs have been shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The bound in Theorem 7 is tight, as can be seen from the graph in Fig. 9, for which the maximum matching has size n−1 4 . Actually this is a Gabriel graph of maximum degree four which is a tree.…”
Section: 2mentioning
confidence: 78%
See 2 more Smart Citations
“…The bound in Theorem 7 is tight, as can be seen from the graph in Fig. 9, for which the maximum matching has size n−1 4 . Actually this is a Gabriel graph of maximum degree four which is a tree.…”
Section: 2mentioning
confidence: 78%
“…We also showed that n−1 2 points are necessary and n − 1 points are sufficient to block 0-TD. In [4] it is shown that 0-TD has a matching of size n−1 3 .…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Lemma 1 (Babu et al [8]). Let P be a set of points in the plane, and let p and q be any two points in P .…”
Section: Preliminariesmentioning
confidence: 99%
“…In fact, they might fall short of being triangulations. As discussed by Drysdale [22] and Chew [18] (see also [7]), they are plane graphs that consist of a "support hull" which need not be convex, and a complete triangulation of the interior (an explicit proof can be found in [8]). This anomaly is often remedied by surrounding the point set with a large bounding triangle.…”
Section: Introductionmentioning
confidence: 99%